Viewable Terrestrial Mammals along the Nature Trails at the Lowland Tropical Forests of Western Sabah, Malaysia Borneo - Lim, Wing Shen; Mojiol, Andy Russel; Bernard, Henry; Matunjau, Christopher A.; Nair, Guptah V. G. (Bogor Agricultural University, Indonesia, 2024)
The information related to the species of terrestrial mammals that can be detected along the nature trails established in the lowland tropical forests of Western Sabah remains scarce at this moment. The camera trapping surveys were commenced at the Tenghilan Community Forest (TCF), Kawang Forest Reserve (KFR), and the urban forest of Universiti Malaysia Sabah (UMS) to investigate the terrestrial mammal species that could be observed along the local trails. A total of 20 terrestrial mammal species belonging to 13 different families were observed in 2,077 trap nights, where most of them were validated to be non-threatened (n = 16 or 80.0%) and omnivorous (n = 13 or 65.0%) species. Twelve species were found along the nature trails in TCF (H’ = 2.223; 1-D = 0.8650) and KFR (H’ = 1.730; 1-D = 0.7078), whereas seven species were detected along the trails in the urban forest of UMS (H’ = 1.217; 1-D = 0.5567). The differences in the mammalian composition, diversity richness, and distribution evenness between these three study sites were validated as significant (p<0.05). The present findings emphasize that these three study sites are favorable habitats for four threatened species. Hence, conservation efforts are needed to protect these terrestrial mammal species from facing extinction risks in future.